THE EFFECT OF COOPERATIVE INTEGRATED READING AND COMPOSITION LEARNING METHOD TOWARDS FABLE WRITING SKILLS - Desri Arwen; Saiful Haq (University of Kuningan, 2021)
Abstract: The purpose of this study was to determine the effect of using the cooperative integrated reading and composition method on learning outcomes to write fables in class VIII students at MTs Daarul Muqimin Buaran Jati, Tangerang Regency. students think learning to write fables is boring, students don't think creatively in learning to write fables, students find it difficult to find creative writing ideas, use less effective learning media, and inappropriate writing learning methods. The method used in this study is a quasi-experimental method by conducting a pretest and posttest in two groups. This type of experimental research method uses a nonequivalent control group design, where the experimental class is treated and the control class is not treated. This nonequivalent control group design is almost the same as the pretest and posttest control group designs, only in this design the experimental and control groups are not chosen randomly. Data collection techniques using tests. The data analysis technique was started from normality test, homogeneity test, and continued with hypothesis testing. From the research results obtained tcount 2.061> ttable 1.9987. So it can be concluded that there are differences in learning outcomes between the control class and the experimental class. Thus, the results of the study using the CIRC (cooperative integrated reading and composition) method showed an increase in the ability to write fables for the students.